Impact of Fiscal Transfers and Local Revenue Accountability on Community Welfare in Indonesia - Muhammad Herdyan Summana Isman; Roy Valiant Salomo; Muhammad Rafi Bakri (Owner : Riset dan Jurnal Akuntansi, 2025)
Community welfare is a national goal outlined in the Preamble of the 1945 Constitution. The Human Development Index (HDI) serves as a key indicator for measuring welfare across three dimensions: health, education, and a decent standard of living. This study aims to analyze the impact of fiscal transfers—General Allocation Fund (DAU), Special Allocation Fund (DAK), and Revenue Sharing Fund (DBH)—along with Local Own-Source Revenue (PAD) on HDI at the provincial level in Indonesia. The research employs a quantitative approach using panel data from all districts and cities in Indonesia for the period 2019–2023, resulting in 2,540 observations collected through a census method. Data analysis is conducted using Fixed Effect Model (FEM) regression to assess both direct effects and the moderating role of fiscal accountability mechanisms, measured by the Government Agency Performance Accountability System (SAKIP) and internal audit (APIP) scores. The findings reveal that PAD and DAK significantly improve HDI, while DAU has no significant effect. Furthermore, higher levels of fiscal accountability strengthen the effectiveness of fiscal transfers in enhancing community welfare. Conversely, weak financial governance and a lack of transparency hinder the optimal utilization of fiscal resources. This study concludes that strengthening oversight, financial governance, and accountability mechanisms is essential to maximizing the benefits of fiscal decentralization, ensuring more equitable resource distribution, and promoting sustainable improvements in community welfare.